Modifications of the Prothrombin Active Site S4 Subpocket Confer Resistance to Dabigatran - Strijbis, Viola J.F.; Cheung, Ka Lei; Veizaj, Dejvid; Rutten, Tessa; de Bruin, Boris; Reitsma, Pieter H.; Verhoef, Daniël; Bos, Mettine H.A. (Thrombosis and Haemostasis, 2025)
Direct anticoagulants inhibit coagulation serine proteases by reversibly engaging their active site with high affinity. By modifying the S4 active site subpocket of factor (F)Xa, we introduced inhibitor resistance while preserving catalytic activity. Given the homology between FXa and thrombin in active site architecture and direct anticoagulant binding, we have targeted the S4 subsite to introduce inhibitor resistance in (pro)thrombin.Recombinant prothrombin variants were generated in which I174 was substituted or sequence R92-N98 was exchanged with that of human kallikrein-3.Specific prothrombin clotting activity of the variants was 6-fold (intrinsic clotting) to 10-fold (extrinsic clotting) reduced relative to wild-type prothrombin. Further analyses revealed that modification of the S4 subsite hampers fibrinogen and thrombomodulin-mediated protein C conversion by thrombin. Consistent with this, the thrombin variants displayed a reduced catalytic efficiency toward the peptidyl substrate used in thrombin generation assessments. The variants displayed a 2-fold reduced sensitivity for dabigatran relative to wild-type prothrombin, while argatroban inhibition was unaffected. Analyses using a purified component system revealed an up to 24-fold and 4-fold reduced IC50 for inhibition of thrombin by dabigatran and argatroban, respectively. Molecular dynamics (MD) simulations of both dabigatran-bound and unbound (apo) modified thrombin variants indicated these to comprise a larger inhibitor binding pocket relative to wild-type thrombin and display reduced inhibitor binding. As a net effect, (pro)thrombin variants with S4 subsite modifications supported detectable fibrin formation at therapeutic dabigatran concentrations.Our findings provide proof-of-concept for the engineering of thrombin variants that are resistant to direct thrombin inhibitors by modulating the S4 subsite.
Keywords: anticoagulants; direct thrombin inhibitors; anticoagulant reversal agents; serine proteases; recombinant fusion proteins